Determination of monosaccharide composition of kefiran using HPLC - Koçak, Çağdaş (Array, 2020)
Kefiran is an exopolysaccharide (EPS) produced by specific microorganisms in the kefir grain. In this research, kefir grain was activated in various carbon sources (glucose, galactose or lactose) containing medium. The monosaccharides composition of the formed kefiran were determined by a high performance liquid chromatography (HPLC). HPLC with refractive index (RI) detector was used in order to make qualitative and quantitative analysis of sucrose, glucose, galactose, arabinose, xylose, and ribose present in kefiran. Also, the physical properties of differently kefiran formed were determined. The amount of kefiran in the control group and in the sample from the galactose containing medium were determined to be 511.00 and 610.55 mg/L, respectively. The kefiran form obtained from the medium containing galactose was more positively affected than in other media. The apparent viscosity, at a shear rate of 66.0 s-1of the kefiran produced in glucose containing medium, was determined to be 29.2 mPas. The surface morphologies of different kefirans were analysed and roughness parameters were determined by atomic force microscopy (AFM); the maximum height of lumps ranged from 16.80 to 22.10 nm. In this study, of sucrose, glucose, galactose, arabinose, xylose, and ribose were found in sugar composition in all kefiran samples.